Пошаговое объяснение:
а)4(3х+5)=2(10+6х)
12х+20=20+12х
12х-12х=20-20
0=0
∅
б)4(3-2х)+24=2(3+2х)
12-8х+24=6+4х
-8х+36=6+4х
-8х-4х=6-36
-12х= -30
х= -30÷(-12)
х=2,5
5+a = a+5 a+3 < 5+a 8-x< 8+x
a+6< a+9 d+3 > d-3 b+5 > b-5
7+a = a+7 d-4 < d-1 a > a+9
a+0 < a+9 7-c > 3-c b > b-3
a < a+3 4+b < 5+b c+0 < 3+c
b > b-3 y-2 < y-3 9-c >10-c
c+3= 3+c 7+c >7-c 6+a > 6-a
5-c > 10-c a+c < c+a a > a+4
a > a-3 a+4 > 4-a a-a = 6-6
4(3x+5)=2(10+6x)
12x+20=20+12x
xєR
4(3-2x)+24=2(3+2x)
12-8x+24=6+4x
36-8x+6+4x
-8x-4x=6-36
-12x+-30
x=5/2
Пошаговое объяснение: